Application of Artificial Immune Algorithm (AIA) in solving engineering problems - Lee Wee Leong (2023)
The tittle for this project is 'Application of Artificial Immune Algorithm (AIA) is Solving Engineering Problems'. The outline of this project is design two Graphical User Interfaces (GUI) that can solve two engineering problems based on Artificial Immune Algorithm.